2010
DOI: 10.1097/olq.0b013e3181e50058
|View full text |Cite
|
Sign up to set email alerts
|

STD Screening of HIV-Infected MSM in HIV Clinics

Abstract: Most asymptomatic HIV-infected MSM were screened for syphilis, indicating good provider adherence to this screening guideline. Low screening rates for gonorrhea and chlamydia, especially at rectal and pharyngeal sites, suggest that substantial barriers exist for complying with these guidelines. The moderate to high prevalence of asymptomatic chlamydial and gonococcal infections underscores the importance of screening. A range of clinical quality improvement interventions are needed to increase screening, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 26 publications
1
85
2
Order By: Relevance
“…Compared to other studies of GC and CT screening among MSM [9,10,13], we found that repeat rectal testing or follow-up testing with any anatomic site specimen was suboptimal among men in our study. The high positivity of repeat rectal tests in our study confirmed the importance of repeat rectal testing for both GC and CT and follow-up testing for pharyngeal GC.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Compared to other studies of GC and CT screening among MSM [9,10,13], we found that repeat rectal testing or follow-up testing with any anatomic site specimen was suboptimal among men in our study. The high positivity of repeat rectal tests in our study confirmed the importance of repeat rectal testing for both GC and CT and follow-up testing for pharyngeal GC.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the CDC recommends rectal GC and CT screening of all MSM who report receptive anal sex [2], and previous studies have showed that rectal GC and CT were associated with increased risk for HIV seroconversion among MSM [3,4], rectal GC and CT testing rates have been suboptimal. Reported rectal testing rates varied from 2.3% among HIV-infected MSM who attended HIV clinics to 60% among MSM who attended local public STD clinics [5,7,9,10]. However, most studies of rectal testing among MSM have been done at public STD or HIV clinics or community clinics that were able to perform non-US Food and Drug Administration (FDA)-cleared rectal testing for GC and CT [5-7, 9, 10].…”
mentioning
confidence: 99%
“…137,158,[165][166][167][168][169] Although HCV has emerged as a STI that is largely confined to HIV-positive MSM, and gonorrhoea and chlamydia are frequently identified, 166 syphilis appears to be the most commonly reported STI coinfection among those with HIV. 159,170 Nonetheless, STI testing rates for nongenital gonorrhoea, chlamydia 171,172 and syphilis 173 in MSM with HIV infection remain below recommended levels.…”
Section: Sti Testing Among Hiv-positive Msmmentioning
confidence: 99%
“…In Melbourne, Australia, only 18% of HIVpositive MSM attending a hospital infectious disease clinic were screened for chlamydia and gonorrhoea (Neisseria gonorrhoeae) during a twice-yearly screening period; 7 in eight large HIV clinics in six cities in the United States, the annual screening rate for rectal chlamydia and gonorrhoea among HIV-positive MSM was less than 10%. 9 The Adult Infectious Disease Service at Auckland City Hospital cares for a large number of people living with HIV infection in the Greater Auckland and Northland regions of New Zealand (an adult population of 1.35 million). All new clinic patients are screened for hepatitis A, B and C virus coinfection; those susceptible to hepatitis A or B are immunised.…”
Section: Introductionmentioning
confidence: 99%